(Re)constructing rurality through skilled trades training. Issue 3 (4th May 2017) - Power, Nicole Gerarda
ABSTRACT: There is a growing body of research interrogating the discursive construction of 'rural' in negative terms – as lacking, in decline or in crisis. This paper contributes to this body of literature by taking as its point of departure skilled trades training in Canada's most easterly province, Newfoundland and Labrador. To meet the labour demand associated with industrial projects in rural and remote areas, the provincial government has invested in strategies to encourage youth to enrol in certified training programmes in the skilled trades. This paper examines the contradictory and incomplete ways in which individualized labour market subjects are produced through a combination of economic restructuring and government policy initiatives related to training and apprenticeships, and considers what this means for how young people think about and experience the rural. I argue that rural places are largely framed in economic terms, either as in decline and crisis or as industrial sites of resource extraction, and that by discursively linking youth outmigration and skilled labour shortages, the sustainability of rural places and the province is individualized and downloaded onto youth, ignoring the structured inequalities that mediate access to training and employment.